Impact of insulin therapy before donation on graft outcomes in pancreas transplantation: An analysis of the OPTN/UNOS database. (December 2021) - Montagud-Marrahi, Enrique; Amor, Antonio J.; Molina-Andujar, Alicia; Cucchiari, David; Revuelta, Ignacio; Esforzado, Nuria; Cofan, Frederic; Oppenheimer, Federic; Torregrosa, Vicens; Casals, Joaquim; Ferrer, Joana; Esmatjes, Enric; et al.
Abstract: Aims: Information on the impact of insulin therapy before pancreas donation on pancreas outcomes is scarce. We aim to explore the influence of insulin therapy before donation on recipient and pancreas graft survival. Methods: Registry study including 12, 841 pancreas recipients from the OPTN/UNOS registry performed between 2000 and 2017. Inverse probability of treatment weighting (IPTW) was used to account for covariate imbalance between recipients from a donor with and without insulin requirements. Results: A total of 7765 (60%) patients received a pancreas from a donor with insulin before donation (IBD). Pancreas graft survival (death-censored) was similar between recipients from IBD and non-IBD donors at 1, 5 and 10 years (89% vs 89%, 78% vs 79 and 69% vs 70%, respectively, P = 0.35). Recipients from IBD donors presented a similar 90-days pancreas graft survival. After IPTW weighting, IBD donors were neither associated with any post-transplant surgical complication (HR 1.11 [95% CI 0.98–1.24], P = 0.06), nor with risk for recipient death (HR 0.94 [95% CI 0.85–1.04], P = 0.26), nor pancreas graft failure (HR 1.06 [95% CI 0.98–1.16], P = 0.15). Conclusions: Insulin therapy before donation in accepted pancreas donors was not associated, per se, with an impaired pancreas graft and patient survival.